Malignant Brenner tumor of the ovary: Review and case report - Lang, Susan M. (Gynecol Oncol Rep, 2017)
Ovarian neoplasms are a heterogeneous group of tumors with varying incidence in the general population. The most common are the surface epithelial tumors which include transitional cell tumors. Transitional cell tumors include both transitional cell carcinoma and Brenner tumor. The vast majority of Brenner tumors are benign, often incidental findings; however, malignant Brenner tumors (MBT) do occasionally occur. MBT present similarly to other ovarian neoplasms with abdominal pain and bulk symptoms. On imaging, these tumors demonstrate nonspecific findings. Microscopically, they demonstrate areas of conventional benign Brenner tumor juxtaposed with regions of frank malignancy showing marked cytologic atypia and infiltration. There is no consistent tumor marker for these tumors, but CA-125, CA 72-4 and SCC have been reported in singular instances. Tumors express several immunohistochemical markers of urothelial differentiation including uroplakin III, thrombomodulin, GATA3, p63, as well as cytokeratin 7. The primary treatment modality is surgical excision. Due to their rarity, the precise role and regimen of adjuvant chemo-radiation therapy for MBT has not been established. We herein review a case of MBT with emphasis on primary treatment and treatment of recurrent disease, including the use of adjuvant pelvic radiation, discuss the current state of the literature and standards of practice regarding this malignancy.